Iodine ion electrochemiluminescence sensor, preparation method and application thereof

CN117030686BActive Publication Date: 2026-10-27CHONGQING MEDICAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310916184.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2026-10-27
Estimated Expiration
2043-07-24

AI Technical Summary

Technical Problem

但其检测灵敏度和便捷性都受到限制,因此开发灵敏、高效的碘离子检测方法成为必要

Benefits of technology

[0034]1.本专利成功开发了一种新型材料,并制备了新型I-电化学发光传感器。利用GSH-AgNCs@ZIF-8和Zn-TCPP等体积掺杂制备的新型传感器通过AgNCs高效专一催化和Zn修饰TCPP发光增强原理,大大提高了I-检测灵敏度和选择性,实现了对I-特异而稳定的检测。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117030686B_ABST
    Figure CN117030686B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrochemical analysis and detection, and particularly relates to an iodine ion electrochemiluminescence sensor and a preparation method and application thereof. The application assembles a metal organic framework and glutathione silver clusters to form a novel material GSH-AgNCs@ZIF-8, and innovatively mixes a new ECL luminophore tetracarboxyphenyl zinc porphyrin with the novel material to obtain a novel luminous composite material capable of adjusting potential and enhancing luminescence, and the novel luminous composite material is used for detecting iodine ions in food and urine. The application first uses a mixed solution of TCPP-Zn and GSH-AgNCs@ZIF-8 to modify the surface of a working electrode, not only develops a novel ECL luminescence system, but also constructs a novel sensor, and provides a new idea for establishing a new ECL luminescence system and detecting small molecules.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical analysis and detection technology, specifically relating to an iodide ion electrochemiluminescence sensor, its preparation method, and its application. Background Technology

[0002] Electrochemiluminescence (ECL) has attracted widespread attention in bioanalysis, clinical diagnostics, and food testing due to its advantages of low background signal, low operating cost, and high controllability. Traditional ECL emitters have the advantage of high luminescence efficiency, but they generally have high biotoxicity and are difficult to synthesize. Therefore, there is an urgent need to find a novel ECL emitter.

[0003] Porphyrins are a class of macrocyclic heterocyclic compounds with highly conjugated structures. The methylene group on the porphyrin ring can connect to different substituents, and the four central nitrogen atoms can combine with metal ions to form stable organic complexes, thus exhibiting flexible tunability and diversity. Some studies have shown that introducing zinc into organic light emitters to form zinc complexes can improve their optical performance. Studies of tetraphenylporphyrin and its zinc complex light emitters revealed that the generation pathway of the excited state after zinc coordination is altered, thereby improving ECL performance. This is because some TCPP-Zn is occupied by zinc ions linked to the pyrrole ring. Zinc ions donate electrons to the porphyrin molecule and also accept lone pairs of electrons from the N atoms of the pyrrole ring; the formation of delocalized π bonds allows electrons to flow easily in the delocalized π system. These studies indicate that the participation of zinc complexes can improve or optimize the ECL performance of the original light emitter, which is of great significance for improving ECL sensing sensitivity. Metal-organic frameworks (MOFs) are microporous crystalline materials self-assembled from metal ions and organic links. They possess advantages such as large internal surface area, tunable size, and ease of modification. Their inherent ordered porosity provides rapid diffusion channels, facilitating electron transfer. Nanoscale MOF materials combine the advantages of nanomaterials with those of MOFs, attracting significant attention in fields such as biosensing. Metal nanoclusters are a class of ultra-small metal nanomaterials that have garnered particular attention in the field of electroluminescence (ECL) due to their "molecular-like" luminescent properties.

[0004] Iodine is one of the essential trace elements for the human body, playing a vital role in growth and metabolism. With the continuous changes in dietary structure, iodine intake has become a hot topic. When the iodine content in food is low, the human body often experiences iodine deficiency symptoms, mainly manifested as goiter and abnormal growth and development of the nervous system in children, and varying degrees of cretinism in adults. Therefore, developing an efficient and rapid method for detecting iodine in urine and food is of great significance. Currently, methods for detecting iodine include colorimetric, FL, CL, and electrochemical detection. However, their sensitivity and convenience are limited, making the development of a sensitive and efficient method for detecting iodide ions necessary. Summary of the Invention

[0005] In view of this, one of the objectives of this invention is to provide an iodide ion electrochemiluminescence sensor. This invention uses iodide ions as the target analyte, a zinc porphyrin complex as the electrochemiluminescent agent, and selects classic glutathione-stabilized silver nanoclusters (GSH-AgNCs) as a model. A composite nanomaterial (GSH-AgNCs@ZIF-8) constructed with imidazole MOF (ZIF-8) is then used as a catalyst to further construct the ECL sensor. This novel ECL system is simple in design, easy to use, has minimal interference with analytes, and achieves detection of iodide (I- ions) at a low limit of detection. - High-efficiency detection.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] An iodide ion electrochemiluminescence sensor is provided, wherein the working electrode surface is modified with a mixed solution of an electrochemiluminescent agent and GSH-AgNCs@ZIF-8; the electrochemiluminescent agent is TCPP-Zn; the TCPP-Zn is prepared by TCPP and ZnCl2; and the GSH-AgNCs@ZIF-8 is prepared by AgNO3, GSH, Zn(NO3)2 and 2-methylimidazole.

[0008] The aforementioned GSH-AgNCs@ZIF-8 is a composite nanomaterial exhibiting both catalytic and luminescent effects. This paper describes the preparation of MOF nanomaterials composed of mixed metal nanoclusters through coordination self-assembly. This not only restricts the vibration and rotation of small ligands in the metal nanoclusters, reducing non-radiative transitions, but also, due to the spatial distribution of the metal nanoclusters, mitigates the self-quenching effect to some extent, thereby significantly improving the efficiency of the metal nanoclusters.

[0009] Because iodide ions react with tetracarboxyphenylporphyrin (TCPP) to produce singlet oxygen ( 1 O2 undergoes a redox reaction in a slightly acidic environment, causing the singlet oxygen produced by porphyrin to act in this way, thus quenching it and enabling the detection of I- by ECL technology.

[0010] Furthermore, in the mixed solution, the volume ratio of TCPP-Zn to GSH-AgNCs@ZIF-8 is 1:1.

[0011] Furthermore, the GSH-AgNCs@ZIF-8 has a rhombic polyhedral structure; the TCPP-Zn is a strip-shaped sheet.

[0012] The second objective of this invention is to provide a method for preparing the iodine ion electrochemiluminescence sensor described in the first objective.

[0013] To achieve the above objectives, the present invention adopts the following technical solution:

[0014] The preparation method of the iodide ion electrochemiluminescence sensor includes the following steps:

[0015] (1) Preparation of GSH-AgNCs@ZIF-8: AgNO3 and GSH were mixed and reacted with ultrapure water and NaOH respectively. After the reaction solution was dialyzed, Zn(NO3)2 was added, and the mixture was sonicated, pH adjusted and centrifuged to obtain the precipitate. After methanol was added to the precipitate, 2-methylimidazole and Zn(NO3)2 were added in sequence under sonication and allowed to stand to obtain the GSH-AgNCs@ZIF-8.

[0016] (2) Preparation of Zn-TCPP: TCPP and DMF are mixed and ultrasonicated, and then ZnCl2 and BPDC are added sequentially while heating and stirring to obtain Zn-TCPP;

[0017] (3) The GSH-AgNCs@ZIF-8 prepared in step (1) and the Zn-TCPP prepared in step (2) are mixed at a volume ratio of 1:1 to obtain a mixture; the mixture is dropped onto the surface of the working electrode to obtain the iodine ion electrochemiluminescence sensor.

[0018] Furthermore, in step (3), the amount of the mixture added is 8 μL.

[0019] Further, in step (3), the TCPP-Zn solid obtained in step (2) is dissolved in ultrapure water to obtain a dispersion with a concentration of 0.2 mg / mL.

[0020] Furthermore, in step (3), the GSH-AgNCs@ZIF-8 with a concentration of 0.2 mg / mL obtained in step (1) needs to be sonicated to obtain a homogeneous solution before being mixed with TCPP-Zn dispersion.

[0021] As a preferred technical solution, step (1) is as follows: AgNO3 and GSH are mixed and stirred evenly, then ultrapure water is added. The mixture is stirred at room temperature to form a white hydrogel. NaOH is then added to dissolve the hydrogel into a colorless and transparent liquid. The mixture is then stirred vigorously at 100°C for 7 hours and incubated at 5°C for 12 hours. After dialyzing for 1 hour, 5 mL of the solution is taken and mixed with Zn(NO3)2. The mixture is then sonicated for 30 minutes, and the pH is adjusted to 5.0 with NaOH. The precipitate is collected after centrifugation three times. Methanol is added to the precipitate, and 2-methylimidazole and Zn(NO3)2 are added sequentially under sonication. The mixture is allowed to stand at 37°C for 12 hours to form GSH-AgNCs@ZIF-8. The precipitate is collected by centrifugation and washing, and dispersed in 4 mL of ultrapure water. The precipitate is stored at 4°C in the dark for later use.

[0022] As a more preferred technical solution, step (1) is as follows: 1.5 mL AgNO3 (concentration of 20 mM) and 1.8 mL GSH (concentration of 50 mM) are mixed and stirred evenly. Then 26.7 mL of ultrapure water is added and stirred at room temperature to form a white hydrogel. Then 200 μL NaOH (concentration of 1 M) is added to the white hydrogel to dissolve it into a colorless and transparent liquid. Then the mixture is stirred vigorously at 100 °C for 7 h and incubated at 5 °C in a refrigerator for 12 h. After dialyzing with a 1000 Da dialysis bag for 1 h, 5 mL of the solution was taken and mixed with 400 μL of Zn(NO3)2 (235.3 mmol / L). The mixture was then sonicated for 30 min, and the pH was adjusted to 5.0 with NaOH. After centrifugation three times, the precipitate was collected. 1 mL of methanol was added to the precipitate, and under sonication, 4 mL of 25 mM 2-methylimidazole and 4 mL of 25 mM Zn(NO3)2 were added sequentially. The mixture was allowed to stand at 37 °C for 12 h to form GSH-AgNCs@ZIF-8. After centrifugation and washing, the precipitate was collected and dispersed in 4 mL of ultrapure water and stored at 4 °C in the dark for later use.

[0023] As a preferred technical solution, step (2) is as follows: TCPP and DMF are added to a round-bottom flask and sonicated to make it a homogeneous solution; then the round-bottom flask is placed on an oil bath and ZnCl2 is added while stirring; then BPDC is added and heated while stirring to 150°C, and the reaction is stirred for 1 hour (the solution color changes from red to brown during heating); the resulting solution is centrifuged, washed three times with ethanol, the precipitate is collected, and dried under vacuum at 45°C to obtain Zn-TCPP, which is a brown solid.

[0024] The third objective of this invention is to provide a method for detecting iodine ion content in food and / or urine using the aforementioned iodine ion electrochemiluminescence sensor. This novel sensor, through the efficient and specific catalysis of AgNCs and the Zn-modified TCPP luminescence enhancement principle, significantly improves the iodine ion content... - The detection sensitivity and selectivity enable specific and stable trace detection of iodide ions, with a detection limit as low as 3.3 pM.

[0025] To achieve the above objectives, the present invention adopts the following technical solution:

[0026] The method for detecting iodine ion content in food and / or urine using the iodine ion electrochemiluminescence sensor described above employs a three-electrode system to detect the sample and calculates the iodine ion content in the sample using a standard curve; the working electrode of the three-electrode system is the iodine ion electrochemiluminescence sensor described in the first objective.

[0027] Furthermore, the reference electrode is Ag / AgCl soaked in saturated KCl solution; the counter electrode is platinum wire.

[0028] Furthermore, potassium persulfate is used as a co-reactant; the pH value of the co-reactant is 6.8.

[0029] Furthermore, the iodide ion concentration is 1×10 -11 M~1×10 -5 Within the range M, the standard curve is I = 3975.39 - 532.79lgc,R 2 =0.9987 where I represents ECL intensity, c represents iodine ion concentration, and R represents correlation coefficient.

[0030] Furthermore, the sample to be tested is urine containing iodide ions and / or food, including milk, biscuits and / or seaweed.

[0031] Furthermore, when the sample to be tested is urine, the urine needs to be heated and centrifuged before iodine ions are extracted for detection.

[0032] This patent employs a simple method to assemble a metal-organic framework with a glutathione silver cluster to form a novel material, GSH-AgNCs@ZIF-8. Simultaneously, it innovatively mixes this material with a novel ECL luminescent material, tetracarboxyphenyl zinc porphyrin, resulting in a novel luminescent composite material with adjustable potential and enhanced luminescence. This composite material is then used for the detection of iodide ions in food and urine. This patent is the first to apply this hybrid material as a highly efficient luminescent material in the construction of an electrochemiluminescence sensing system. Under optimized conditions, the ECL sensor of this invention detects iodide ions in a linear range of 10 pM to 10 μM. - It exhibits excellent response, and the detection method demonstrates excellent selectivity, stability, and sensitivity.

[0033] The beneficial effects of this invention are as follows:

[0034] 1. This patent successfully developed a novel material and prepared a novel I - Electrochemiluminescence sensor. A novel sensor fabricated using isovolute doping of GSH-AgNCs@ZIF-8 and Zn-TCPP significantly improves IL by utilizing the efficient and specific catalysis of AgNCs and the luminescence enhancement principle of Zn-modified TCPP. - Detection sensitivity and selectivity enable the detection of I - Specific and stable detection.

[0035] 2. The novel sensor provided by this patent has an extremely low detection limit, enabling the electrodes to handle trace amounts of I - The sensor has a detection limit as low as 3.3 pM.

[0036] 3. This application not only develops a novel ECL luminescence system, but also constructs a novel sensor, providing new ideas for the establishment of new ECL luminescence systems and the detection of small molecules.

[0037] 4. This invention detects I in food and urine samples. - This demonstrates the feasibility and potential application value of this sensing strategy in practical use, and lays the foundation for establishing a system for detecting I - Sensors for small molecules provide a new approach to electrochemiluminescence. Attached Figure Description

[0038] Figure 1 SEM image of GSH-AgNCs@ZIF-8 nanomaterial (ZIF-8);

[0039] Figure 2 SEM image of GSH-AgNCs@ZIF-8 nanomaterial (GSH-AgNCs);

[0040] Figure 3 SEM image of GSH-AgNCs@ZIF-8 nanomaterial (GSH-AgNCs@ZIF-8);

[0041] Figures 4-8 The image shows the EDS element mapping analysis results for GSH-AgNCs@ZIF-8, where... Figures 4-8 These represent the corresponding elements Ag, S, N, Zn, and O, respectively.

[0042] Figure 9 Elemental distribution diagram of GSH-AgNCs@ZIF-8;

[0043] Figure 10 The images show the FT-IR spectra of the relevant materials; where (a): ZIF-8, (b): GSH-AgNCs, (c): GSH-AgNCs@ZIF-8;

[0044] Figure 11 The images show the UV-Vis spectra of the relevant materials; where (a): ZIF-8, (b): GSH-AgNCs, (c): GSH-AgNCs@ZIF-8;

[0045] Figures 12-14 SEM images of Zn-TCPP;

[0046] Figures 15-18 The image shows the element mapping analysis results of Zn-TCPP, where... Figures 15-18 These represent the corresponding elements Zn, C, N, and O, respectively.

[0047] Figure 19 This is a diagram showing the element distribution of Zn-TCPP.

[0048] Figure 20The images show the FT-IR spectra of the relevant materials; where (a): TCPP-Zn, (b): TCPP;

[0049] Figure 21 The images show the UV-Vis spectra of the relevant materials; where (a): TCPP-Zn, (b): TCPP;

[0050] Figure 22 The fluorescence spectrum of TCPP-Zn is shown below; where (a): TCPP-Zn, (b): TCPP;

[0051] Figure 23 Comparison of ECL effects between single-modification and doping-modification pairs; where, (a): TCPP-Zn, (b): GSH-AgNCs@ZIF-8, (c): ECL of mixed doping modification of the two materials;

[0052] Figure 24 A comparison chart of ECL intensities at different pH values;

[0053] Figure 25 The graph shows the effect of the material dosage on the ECL strength.

[0054] Figure 26 The CV curve is shown in Example 4; where (a): bare GCE, (b): GSH-AgNCs@ZIF-8 / GCE, (c): TCPP-Zn / GCE, (d): GSH-AgNCs@ZIF-8 / TCPP-Zn / GCE;

[0055] Figure 27 The image shows the EIS results for Example 4; where (a): bare GCE, (b): GSH-AgNCs@ZIF-8 / GCE, (c): TCPP-Zn / GCE, (d): GSH-AgNCs@ZIF-8 / TCPP-Zn / GCE;

[0056] Figure 28 For different concentrations of I - The ECL signal response results after the electrode was added;

[0057] Figure 29 The graph shows the linear relationship between iodine ion concentration and ECL intensity.

[0058] Figure 30 The biosensor prepared in Example 1 is sensitive to the same concentration of I - A diagram of continuous emission signals;

[0059] Figure 31 The biosensor prepared in Example 1 responds to different concentrations of I -The graph shows the emission signals of the light source; where (a): 1 μM, (b): 10 nM, (c): 10 pM;

[0060] Figure 32 This is a graph showing the selectivity results of the biosensor prepared in Example 1;

[0061] Figure 33 This diagram illustrates the preparation process of the electrochemically modified sensor and the iodine ion detection principle of the present invention. Detailed Implementation

[0062] The technical solution of the present invention will be described more clearly and completely below with reference to specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0063] In this embodiment of the invention, glutathione (reduced form): CAS 70-18-8, purity 98%, manufacturer: Aladdin, specification: 25g; AgNO3: CAS 7761-88-8, purity AR, manufacturer: Sinopharm Chemical Reagent Co., Ltd.; NaOH: CAS 1310-73-2, purity >98%, manufacturer: BBI Life Sciences; 2-methylimidazole: CAS 693-98-1, purity 98%, manufacturer: damas-beta; BPDC: CAS 787-70-2, purity >98%, manufacturer: Sangon Biotech (Shanghai) Co., Ltd.; DMF: CAS 68-12-2, purity >99.5%, manufacturer: Sangon Biotech; ZnCl2: CAS 7646-85-7, purity >98%, manufacturer: Sangon Biotech. Biotech; all other reagents were analytical grade and required no further purification. All experiments used Milli-Q water (>18.2 MΩcm). -1 ).

[0064] In this embodiment of the invention, the co-reactant K2S2O8 is prepared as follows: a PBS solution containing 0.1M KCl (0.1M, pH 6.8) is prepared from a stock solution of 0.1M Na2HPO4 and 0.1M KH2PO4 and KCl; a K2S2O8 solution (0.1M, pH 6.8) is prepared using the PBS solution.

[0065] In this embodiment of the invention, an MPI electrochemiluminescence analyzer (manufactured by MPI-A Xi'an Ruimai Instrument Co., Ltd.) was used to record the ECL signal, with the photomultiplier tube set to 800V. Electrochemical analysis was performed using a CHI electrochemical analyzer (model CHI 660E, manufactured by Shanghai Chenhua Instrument Co., Ltd.). TEM measurements were conducted on a JEOL JEM-2010 (200kV), and Fourier transform infrared (FT-IR) spectroscopy was performed using a SEM (SU8010, Hitachi, Tokyo, Japan) and an EDS (X-MaxN, Oxford Instruments, UK) on a Thermo Scientific Nicolet 6700 in the United States to study characteristic functional groups on the surface. Ultraviolet-visible (UV-vis) absorption spectra, as well as excitation and emission spectra, were recorded on a UV-vis spectrometer (Shimadzu, Japan) and a fluorescence spectrophotometer (SpectraMax iD3, Molecular Devices), respectively.

[0066] In this embodiment of the invention, a traditional three-electrode system is used. The working electrode is a glassy carbon electrode (GCE, 4 mm in diameter), the reference electrode is Ag / AgCl soaked in saturated KCl solution, and the other counter electrode is a platinum wire.

[0067] In this embodiment of the invention, I - The principle of ECL detection by the electrode is as follows:

[0068] Based on previous reports, this patent investigated the cathodic ECL behavior of GSH-AgNCs@ZIF-8 on a GCE under the condition of potassium persulfate (K2S2O8) as a co-reactant. During negative potential scanning, GSH-AgNCs@ZIF-8 can release electrons for oxidation, forming positively charged GSH-AgNCs@ZIF-8. ·+ Simultaneously, the co-reactant S2O8 2- It is electro-oxidized to form sulfate SO4 ·- Then sulfate SO4 ·- Deprotonation from highly reducing radical sulfates. GSH-AgNCs@ZIF-8 can be reduced via sulfate. ·+ GSH-AgNCs@ZIF-8 generated in an excited state * Then the excited state returns to the ground state and releases energy in the form of light, which is the result of ECL emission.

[0069] (1)GSH-AgNCs@ZIF-8-e - →GSH-AgNCs@ZIF-8 ·+ ;

[0070] (2)S2O8 2- +e -→SO4 2· +SO4 ·- ;

[0071] (3) GSH-AgNCs@ZIF-8 ·+ +SO4 ·- →GSH-AgNCs@ZIF-8 * +SO4;

[0072] (4) GSH-AgNCs@ZIF-8 * →GSH-AgNCs@ZIF-8+hv.

[0073] First, tetracarboxyphenylporphyrin (TCPP) in Zn-TCPP acts as the luminescent host, and cathode luminescence is formed using potassium persulfate (K2S2O8) as a co-reactant. Zn-TCPP and O2 are reduced to the corresponding anionic radical (Zn-TCPP). ·- O2 ·- Simultaneously, the co-reactant K2S2O8 is also reduced to the corresponding sulfate radical ions (SO4). ·- The resulting anionic free radical Zn-TCPP ·- and O2 ·- The corresponding excited state Zn-TCPP is obtained through electron transfer. * , 1 O2 * and anion Zn-TCPP 2- O2 2- Finally, it emits overlapping cathode ECL light. Iodine ions (I - Iodide ions, as the most typical detectable anion, play a crucial role in the metabolism of organisms in nature and the development of the human brain. Iodide ions react with tetracarboxyphenylporphyrin to produce singlet oxygen (…). 1 O2) undergoes a redox reaction in a slightly acidic environment (pH = 6.8), allowing the singlet oxygen produced by porphyrin to act in this form, quenching ECL to achieve I - The detection.

[0074] (1) O2+e - →O2 ·- ;

[0075] (2) TCPP-Zn + →TCPP-Zn ·- ;

[0076] (3)S2O8 2- +e - →SO4 ·- +SO4 2- ;

[0077] (4) TCPP-Zn ·- +O2 ·- →TCPP-Zn * +O2 2- or TCPP-Zn 2- +1O2 * ;

[0078] (5) TCPP-Zn 2- +TCPP-Zn→TCPP-Zn ·- ;

[0079] (6) TCPP-Zn ·- +SO4 ·- →TCPP-Zn * +SO4 2- ;

[0080] (7) 1 O2 * → 3 O2+hv;

[0081] (8) TCPP-Zn * →TCPP-Zn+hv;

[0082] (9)I -+1 O2→I3 - + 3 O2.

[0083] The asterisk (*) above indicates the excited state of the substance, representing the excited state of the substance.

[0084] Example 1. Fabrication of an electrochemically modified sensor

[0085] 1. Preparation of GSH-AgNCs@ZIF-8

[0086] First, 1.5 mL of AgNO3 (20 mM) and 1.8 mL of GSH (50 mM) were mixed and stirred thoroughly. Then, 26.7 mL of ultrapure water was added and stirred at room temperature to form a white hydrogel. Subsequently, 200 μL of NaOH (1 M) was added to the white hydrogel to dissolve it into a colorless and transparent liquid. The mixture was then stirred vigorously at 100 °C for 7 h and incubated at 5 °C for 12 h. After dialyzing with a 1000 Da dialysis bag for 1 h, 5 mL of the solution was taken and 400 μL of Zn(NO3)2 (concentration of 235.3 mmol / L) was added and mixed. The mixture was then sonicated for 30 min, and the pH was adjusted to 5.0 with NaOH. After centrifugation three times, the precipitate was collected. 1 mL of methanol was added to the precipitate, and 4 mL of 25 mM 2-methylimidazole and 4 mL of 25 mM Zn(NO3)2 were added sequentially under sonication. The mixture was allowed to stand at 37 °C for 12 h to form GSH-AgNCs@ZIF-8. After centrifugation and washing, the precipitate was collected and dispersed in 4 mL of ultrapure water and stored at 4 °C in the dark for later use.

[0087] 2. Preparation of Zn-TCPP

[0088] First, take 4 mg of TCPP and 4 mg of BPDC, and add 15 mg of ZnCl2 to 5 mL of ultrapure water. Then, add TCPP to a round-bottom flask and add 24 mL of DMF. Sonicate the solution to make it homogeneous. Then, place the round-bottom flask on an oil bath and add 4 mL of 3 mg / mL ZnCl2 while stirring. Then, add 4 mg of BPDC and heat while stirring to 150 °C. Stir and react for 1 hour (the solution color changes from red to brown during heating). Centrifuge the resulting solution, wash three times with ethanol, collect the precipitate, and dry it under vacuum at 45 °C to obtain a brown solid.

[0089] 3. Fabrication of Electrochemically Modified Sensors

[0090] To fabricate the modified electrode, TCPP-Zn solid was first dissolved in ultrapure water to obtain a dispersion with a concentration of 0.2 mg / mL. Then, GSH-AgNCs@ZIF with a concentration of 0.2 mg / mL was sonicated to obtain a homogeneous solution. Subsequently, the two materials were mixed in equal volumes and sonicated for 5 min. Finally, 8 μL of the mixture was drop-cast onto a clean GCE surface and dried at room temperature for later use.

[0091] The fabrication process of the electrochemically modified sensor and the principle of using this sensor to detect iodide ions are as follows: Figure 33 As shown.

[0092] Example 2. Characterization of GSH-AgNCs@ZIF-8 and Zn-TCPP prepared in Example 1

[0093] In this embodiment, the GSH-AgNCs@ZIF-8 nanomaterials prepared in Example 1 were characterized by SEM and EDS. SEM images are shown below. Figures 1-3 As shown, the results indicate that ZIF-8 has a spindle-shaped structure; GSH-AgNCs has a three-dimensional cluster structure; and GSH-AgNCs@ZIF-8 has a rhombic polyhedral structure. EDS elemental mapping analysis was used to further determine the elemental composition of GSH-AgNCs@ZIF-8, and the results are as follows. Figures 4-8 As shown. From Figures 4-8 As can be seen, O, N, Zn, S, and Ag are uniformly distributed, indicating that the nanoclusters are uniformly distributed during the assembly process. Elemental distribution diagram (STEM-EDS) is shown below. Figure 9 As shown, characteristic peaks for Ag and S can be observed. Both peaks indicate that GSH-AgNCs have been successfully integrated into the assembly. In the FT-IR spectrum, Zn-O shows a peak at 435 cm⁻¹. -1 There is a characteristic contraction vibration peak at this point, indicating that in GSH-AgNCs, the formation of self-assembly depends on COO- and Zn-. 2+ Coordination between them, see Figure 10 Ultraviolet-visible spectrum, such as Figure 11 As shown, the peak of GSH-AgNCs@ZIF-8 is shifted to the right compared to the peaks of ZIF-8 and GSH-AgNCs, indicating the formation of the assembly.

[0094] SEM images such as Figures 12-14 As shown, TCPP has a dispersed structure and an irregular shape. TCPP-Zn exists in the form of strip-like flakes. The synthesis efficiency of TCPP-Zn was further investigated using STEM-EDS element mapping analysis, FTIR, UV-vis, and FL analysis. The element mapping analysis results are shown below. Figure 15-18 As shown, Zn, C, N, and O are uniformly distributed. The EDS results are as follows... Figure 19 As shown, characteristic peaks for Zn, O, C, and N were observed in the EDS spectrum. The FT-IR spectrum is shown below. Figure 20 As shown, at 3430cm -1 and 3310cm -1 The two absorption peaks at 995 cm⁻¹ represent the stretching vibration of OH and the stretching vibration of NH on the carboxyl group. These absorption peaks disappear after TCPP-Zn formation, indicating that the hydrogen proton is replaced by the zinc ion, forming a coordinate bond. On the other hand, at 995 cm⁻¹... -1 A new peak appeared at 966 cm⁻¹, while the vibration peak of the NH plane was at 966 cm⁻¹. -1 The C=O tensile vibration disappears at 1680 cm⁻¹. -1 The intensity decreases over time. This indicates that TCPP-Zn has been successfully synthesized. The UV-Vis spectrum of TCPP-Zn is as follows: Figure 21As shown, the results indicate a strong absorption peak at 330 nm, and four weak Q bands at 522 nm, 582 nm, 603 nm, and 656 nm. This is due to the pp... * The absorption peak reaches 422 nm with the formation of TCPP-Zn, corresponding to the S0→S2 transition, as TCPP-Zn forms. The degeneracy of the two weak Q bands at 576 nm and 611 nm is due to the S0→S1 transition, indicating that the TCPP ligand is metallized by zinc ions during the reaction. In the fluorescence spectrum, TCPP-Zn has absorption peaks at 671 nm and 743 nm. (See [link to fluorescence spectrum]). Figure 22 Compared to the TCPP absorption peak, its absorption peak is increased, confirming the successful synthesis of TCPP-Zn.

[0095] Example 3: Optimization of Experimental Conditions

[0096] Since both GSH-AgNCs@ZIF-8 and Zn-TCPP can improve ECL efficiency, this application compares the ECL efficiency of electrodes modified only with GSH-AgNCs@ZIF-8, electrodes modified only with Zn-TCPP, and novel materials modified with equal-volume doping. The results are as follows: Figure 23 As shown, the photoelectric efficiency of the doped electrode is significantly higher than that of the unmodified electrode, demonstrating the strong advantages of the novel detection system created in this application. The following experiments will also continue to use electrodes modified with the new material.

[0097] To further optimize sensor performance, this embodiment first optimized the pH value of the detection solution, conducting comparative studies within the PBS buffer range (pH = 6.0, 6.5, 6.8, 7.0, 7.2, 7.4). The results are as follows... Figure 24 As shown, the signal was strongest and most stable at pH 6.8, therefore 6.8 was chosen as the optimal pH value for the co-reactant in the experiment. Furthermore, pH 6.8 is a slightly acidic environment, where the singlet oxygen produced by the reaction of iodide ions with tetracarboxyphenylporphyrin (…) 1 O2) allows for better redox reactions in this environment, enabling the singlet oxygen produced by porphyrin to quench ECL and achieve I- detection. Finally, the dosage of the added material was optimized while keeping other conditions constant, and the results are as follows: Figure 25 As shown, analyses were conducted at commonly used doses of 6uL, 7uL, 8uL, and 10uL. Ultimately, it was found that the experimental results were effective and the experimental error was minimized at a dose of 8uL, therefore this was taken as the optimal dose.

[0098] Example 4. Electrochemical and ECL characterization

[0099] In this embodiment, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to record the gradual fabrication process of the sensor in a 1M K3[Fe(CN)6] solution (pH 7.4). The corresponding CV curves are shown below. Figure 26 As shown, a clear redox peak was obtained on the bare electrode (curve a). Due to the increased resistance and decreased conductivity caused by the adhesion of the material, a decrease in the redox peak was observed in TCPP-Zn / GCE and GSH-AgNCs@ZIF-8 / GCE (curves b, c). Modifying the electrode with a mixture of the two materials resulted in increased impedance, decreased current, and a significantly lower redox peak compared to modification with either material alone (curve d). EIS results are shown below. Figure 27 As shown, the results are consistent with CV, indicating the successful fabrication of the biosensor.

[0100] Example 5. ECL Detection

[0101] To evaluate the performance of the ECL sensor fabricated in Example 1 on I - To assess the performance of the detection, this embodiment tested different concentrations of I. - The ECL signal response of the electrode after addition is as follows: Figures 28-29 As shown. With I - Concentration from 10 -11 M rises to 10 -5 M and ECL intensity gradually decrease and show a good linear relationship (I = 3975.39 - 532.79lgc, R). 2 =0.9987), with a detection limit of 3.3 pM (S / N = 3). Compared with existing methods for detecting iodide ions, this sensor has a wider linear response range and an extremely low detection limit. See Table 1. The binding of iodide ions to the high specific surface area of ​​GSH-AgNCs@ZIF-8 and the numerous silver nanoclusters creating contact sites is masked, and the singlet oxygen generated by iodide ions and porphyrin (Zn-TCPP) under acidic conditions (…). 1 O2 undergoes a redox reaction, extinguishing this form of luminescence, thereby achieving highly sensitive detection of I-.

[0102] Table 1. Sensitivity comparison of the ECL sensor of this patent with other methods for determining iodide ions.

[0103]

[0104]

[0105] Example 6. Sensor Stability and Selectivity

[0106] This embodiment verifies the stability and selectivity of the biosensor prepared in Example 1. This biosensor responds to different concentrations of I...- stability such as Figures 30-32 As shown. Among them, the continuous emission signals at the same concentration exhibit almost identical behavior, demonstrating good stability. See [reference needed]. Figure 30 Furthermore, stable luminescence signals were observed when I- concentrations of 1 μM, 10 nM, and 10 pM were tested. (See [link to relevant documentation]). Figure 31 This result indicates that the sensor exhibits good continuous measurement stability and performance at different I concentrations. - Stability of the detection. A 10 μM glucose and Ca2+ concentration was selected. 2+ Mg 2+ SO4 2- and HCO 3- Test the selectivity of the ECL sensor, such as Figure 32 As shown. The results indicate that the ECL signals of each substance are much lower than I. - Furthermore, the response errors of each substance are not significant. This demonstrates that the electrode possesses a specific and powerful Ig. - The detection capability enables stable and continuous I-type detection.

[0107] Example 7. Detection and analysis of urine and commercially available samples

[0108] This embodiment applies the sensor obtained in Example 1 to a real-world application. - The test examined urine and commercially available samples of milk, biscuits, and seaweed for I. - Content. Biscuits and seaweed were dissolved in ultrapure water and ultrasonically dispersed to extract I. - Both samples were then filtered to remove any suspended impurities. Urine samples were heated and centrifuged before iodine ion extraction for detection. Table 2 shows that the recovery rates ranged from 97.6% to 102.1%, with most samples showing iodine ions levels close to the labeled dosage. - The overall detection results for the concentration were good.

[0109] Table 2

[0110] biscuit 40.2 41.2 97.6 milk 394.1 401 98.3 seaweed 323.1 316.4 102.1 urine 472.8 474.2 100.4

Claims

1. An iodide ion electrochemiluminescence sensor, characterized in that, The iodide ion electrochemiluminescence sensor uses a mixed solution of an electrochemiluminescent agent and GSH-AgNCs@ZIF-8 to modify the surface of the working electrode; the electrochemiluminescent agent is TCPP-Zn; the TCPP-Zn is prepared by TCPP and ZnCl2; the GSH-AgNCs@ZIF-8 is prepared by AgNO3, GSH, Zn(NO3)2 and 2-methylimidazole.

2. The sensor according to claim 1, characterized in that, In the mixed solution, the volume ratio of TCPP-Zn and GSH-AgNCs@ZIF-8 is 1:

1.

3. The sensor according to claim 1, characterized in that, The GSH-AgNCs@ZIF-8 has a rhombic polyhedral structure; The TCPP-Zn is a strip-shaped thin sheet.

4. The method for preparing the iodide ion electrochemiluminescence sensor according to claim 1, characterized in that, Includes the following steps: (1) Preparation of GSH-AgNCs@ZIF-8: AgNO3 and GSH were mixed and reacted with ultrapure water and NaOH in sequence. After the reaction solution was dialyzed, Zn(NO3)2 was added, and the mixture was sonicated, pH adjusted, and centrifuged to obtain the precipitate. After methanol was added to the precipitate, 2-methylimidazole and Zn(NO3)2 were added in sequence under sonication, and the mixture was allowed to stand to obtain the GSH-AgNCs@ZIF-8. (2) Preparation of Zn-TCPP: TCPP and DMF are mixed and ultrasonicated, and then ZnCl2 and BPDC are added sequentially while heating and stirring to obtain Zn-TCPP; (3) The GSH-AgNCs@ZIF-8 prepared in step (1) and the Zn-TCPP prepared in step (2) are mixed at a volume ratio of 1:1 to obtain a mixture; the mixture is dropped onto the surface of the working electrode to obtain the iodide ion electrochemiluminescence sensor.

5. The preparation method according to claim 4, characterized in that, In step (3), the amount of the mixture added is 8 μL.

6. A method for detecting iodine ion content in food and / or urine using the iodine ion electrochemiluminescence sensor according to any one of claims 1-3, characterized in that, A three-electrode system is used to detect the sample to be tested, and the content of iodide ions in the sample to be tested is calculated by using a standard curve; the working electrode of the three-electrode system is the iodide ion electrochemiluminescence sensor as described in any one of claims 1-3.

7. The method according to claim 6, characterized in that, The reference electrode is Ag / AgCl soaked in saturated KCl solution; The counter electrode is a platinum wire.

8. The method according to claim 6, characterized in that, Potassium persulfate was used as a co-reactant; the pH value of the co-reactant was 6.

8.

9. The method according to claim 6, characterized in that, Iodide ion concentration at 1×10 -11 M~1×10 -5 Within the range M, the standard curve is I = 3975.39 - 532.79lgc,R 2 =0.9987, where I represents ECL intensity, c represents iodine ion concentration, and R represents correlation coefficient.

10. The method according to claim 6, characterized in that, The test samples are urine containing iodide ions and / or food, including milk, biscuits and / or seaweed.

Citation Information

Patent Citations

  • Preparation method of electrochemiluminescent material based on zinc porphyrin

    CN106977522A

  • Application of two-dimensional metal organic framework zinc porphyrin complex nano material in electrogenerated chemiluminescence detection of miRNA (micro Ribonucleic Acid)

    CN114414557A